Enhanced Customer Interactions through Customer-Centric Technology within a Call Centre - Oodith, Devina (Journal of Economics and Behavioral Studies, 2019)
Customer call centres have become a critical form of service delivery for many organisations hence technological innovations serve as a critical point of contact between the organisation and its customers and can assist in raising the stakes in businesses in terms of customer service delivery (Burgess & Connell, 2004). According to the 2017 Global Customer Experience Benchmarking Report technology has been the number one enabler to positively enhance customer service experience in the last 5 years (Business Tech, 2017). Customers have become so empowered that they expect to have flexibility to contact a business however they choose; either via a telephone, email or Facebook. The key to ensuring satisfaction though is system’s efficiency and ease of use. This study was undertaken in EThekwini (Durban), South Africa and was directed within a Public Sector service environment comprising of four major call centres employing a total of 240 call centre agents. Using simple random sampling, 220 customers were drawn from all consumers subscribing to e-billing in EThekwini (Durban). Data for the customer sample was collected using a precoded, self-developed questionnaire whose psychometric properties were statistically determined. Data was analyzed using descriptive and inferential statistics. The results specify that in terms of customers’ perceptions of the influence of technology, on call centre effectiveness the majority of the customers found it challenging to use the technology and to understand the self-help options that were provided to them by the call centre. There were problems encountered with logging in customer queries and complaints and most customers were dissatisfied with their overall customer experience. Based on the results of the study recommendations have been made to manage the interactions between the customers and call centre’s more proficiently and powerfully.